PRAKTIK BAIK PEMBELAJARAN AGAMA DAN MORAL PADA ANAK USIA 5- 6 TAHUN DI TADIKA PASTI AL-MUKMIN, MALAYSIA - Anjeli, Nur; Tamara, A. Atika; Nurtiyawati; Maharani, Afifah; Izfanna, Duna; Binti Samaun, Siti Salina (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Religious and moral education is one aspect of children's development that is often sidelined. Religious and moral values ​​are part of a child's self-development which starts from an early age. Moral education is carried out to make students civilized and able to become human beings who can adapt to their environment. However, in reality, there are still many students who are found engaging in deviant behavior which ultimately results in moral degradation in students. Schools will be truly meaningful if they implement moral education to students in totality. Islamic religious education for early childhood is also a means to prepare students to understand, recognize, be devout, believe in religious teachings, practice noble Islamic morals from the main sources, namely Al-Quran and hadith, through teaching, mentoring and training activities as well as the use of experience. This study aims to explore good practices in religious and moral learning for children aged 5-6 years in Tadika Pasti Al-Mukmin, Malaysia. The researchers use descriptive qualitative research methods using observation, interviews and documentation methods. While data analysis used qualitative data analysis techniques. Based on the results obtained, the researchers conclude that religious and moral learning is given to children through introductions to God's creation of nature and everything in it. Then, worship is introduced, especially prayer, ablution and daily prayer. Islamic habits are also taught to form good morals. Instilling religion and morals in early childhood is very important because religion and morals are the main foundation in forming a child's character which aims to create humans with noble character and provide the child with provisions when facing life in the following days until he becomes an adult. Keywords: Teaching Moral, Religion, children